Restorative Justice in Resolving Criminal Cases of Child Abuse From an Islamic Legal Perspective - Pratama, Jerry (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Persecution among children requires special attention. Many cases of abuse result in minor injuries, serious injuries, and even death for the victims. Cases of abuse by minors can be caused by several factors, so it became a question whether positive law currently facilitates a restorative justice approach in resolving cases of abuse by minors or whether minors are subject to repressive sanctions per statutory provisions. This research aims to explain the perspective of Islamic law in resolving cases of abuse by minors through a restorative justice approach using normative research methods with a qualitative approach to describe the application of restorative justice in resolving cases of criminal acts of abuse by minors. Based on the research that has been conducted, it was found that Islamic law recognises a restorative justice approach through several mechanisms for resolving abuse cases using mediation and compensation in the form of diyat, providing education and guidance, seeking to protect the rights of minors, and involving the role of the community and stakeholders in the process. This research concludes that Islamic law recognises a restorative justice approach to help resolve cases of abuse by children who conflict with the law and to provide understanding to children so they can understand their mistakes, improve themselves so as not to repeat mistakes, and get a second chance in society. However, it is important to note that the implementation of restorative justice must always take into consideration the rights of victims and the interests of society as a whole.Kekerasan dalam bentuk penganiayaan yang dilakukan oleh anak di bawah umur membutuhkan perhatian khusus, melihat begitu banyaknya kasus penganiayaan yang mengakibatkan luka ringan, luka berat hingga kematian bagi korbannya. Meningkatnya kasus penganiayaan oleh anak di bawah umur bisa disebabkan oleh beberapa faktor sehingga menimbulkan pertanyaan apakah hukum positif saat ini sudah memfasilitasi pendekatan restorative justice dalam penyelesaian kasus penganiayaan oleh anak di bawah umur atau justru anak di bawah umur dijatuhkan sanksi represif sesuai ketentuan perundang-undangan. Tujuan penelitian ini untuk mengemukakan bagaimana prespektif hukum islam dalam menyelesaikan kasus penganiayaan oleh anak di bawah umur melalui pendekatan restoratif justice dengan metode penelitian normatif dengan pendekatan kualitatif untuk menggambarkan penerapan restoratif justice dalam penyelesaian perkara tindak pidana penganiayaan oleh anak di bawah umur. Berdasarkan penelitian yang telah dilakukan didapatkan temuan bahwa hukum Islam mengenal pendekatan restorative justice melalui beberapa mekanisme penyelesaian perkara penganiayaan dengan cara mediasi dan kompensasi berupa diyat, memberikan pendidikan dan pembinaan, mengupayakan perlindungan hak anak di bawah umur dan melibatkan peran masyarakat dan pemangku kepentingan dalam prosesnya. Penelitian ini menyimpulkan hukum Islam mengenal pendekatan restorative justice untuk membantu penyelesaian perkara penganiyaan oleh anak yang berkonflik dengan hukum dalam rangka memberikan pemahaman kepada anak untuk memahami kesalahan mereka, memperbaiki diri, dan mendapatkan kesempatan kedua dalam masyarakat. Namun, penting untuk mencatat bahwa penerapan Restorative Justice harus selalu memperhatikan hak-hak korban dan kepentingan masyarakat secara keseluruhan.